2008
DOI: 10.1155/2009/371901
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Need for Supplemental Oxygen During Airline Flight in Patients with Chronic Pulmonary Disease: A Comparison of Predictive Equations and Altitude Simulation

Abstract: Current screening recommendations for determining which patients require formal assessment of oxygen during flight are inadequate. Predictive equations based on sea level variables provide poor estimates of PaO(2) measured during altitude simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Various proposed equations and single sea-level variables have proven not to predict in-flight hypoxaemia with a satisfactory precision 1 3–5 16 22. Several authors have suggested that exercise-related outcomes may be useful discriminators 4 5 14 24 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various proposed equations and single sea-level variables have proven not to predict in-flight hypoxaemia with a satisfactory precision 1 3–5 16 22. Several authors have suggested that exercise-related outcomes may be useful discriminators 4 5 14 24 25.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to minimise the number of patients needing referral to HAST. Prediction equations, sea level PaO 2 and spirometric values alone have proven not to be reliable tools for estimating the risk of severe in-flight hypoxaemia 1 3–5 16 22. In an algorithm published by the British Thoracic Society (BTS), sea-level oxygen saturation by pulse oximetry (SpO 2 SL ) was used as a discriminating variable,13 and it was recently confirmed that a SpO 2 SL <92% seems to be an appropriate cut-off value for recommending in-flight supplemental oxygen without further pre-flight evaluation 23.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased exercise capacity has been reported in heart failure passengers at high altitudes . Oxygen supplementation is generally recommended in passengers with New York Heart Association (NYHA) class III/IV symptoms, passengers with baseline arterial oxygen saturation of <92%, and those who use oxygen at sea level . Severe decompensated heart failure is an absolute contraindication to air travel .…”
Section: Air Travel and Heart Diseasementioning
confidence: 99%
“…27 Oxygen supplementation is generally recommended in passengers with New York Heart Association (NYHA) class III/IV symptoms, passengers with baseline arterial oxygen saturation of <92%, and those who use oxygen at sea level. 1,2,10,17,28 Severe decompensated heart failure is an absolute contraindication to air travel. 17 Minor hemodynamic alteration and decrease in blood flow has been reported in several cases.…”
Section: Heart Failurementioning
confidence: 99%
“…15 The Aerospace Medical Association 2 and British Thoracic Society (BTS) 4 recommend to perform a hypoxic altitude simulation test (HAST) to assess whether patients need in-flight oxygen supplementation. The HAST is considered the gold standard 11 and it can be done by artificially reducing inspired oxygen to similar levels as those experienced at 2438 m (8000 feet) for 20 min by either reducing the fraction of inspired oxygen to 15% 1,4,7,11 or by reducing atmospheric pressure to 565 Torr (75 kPa) in a hypobaric chamber. 4,11 The normobaric HAST is usually the preferred technique, as it is more accessible and inexpensive than the HAST performed in a hypobaric chamber.…”
Section: Introductionmentioning
confidence: 99%